BCCT learning management: Islamic education’s material in early childhood - Nur Hasanah (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2017)
AbstractThis research is aimed to know the BBCT (Beyond Center and Circle Time) learning management on Early Childhood Islamic Education’ Material in BCC (Bina Citra Cendekia) Ungaran Kindergarten and to know the supporting and unsupporting management factors of Early Childhood Islamic Education’ Material in BCC Ungaran Kindergarten. This research belongs to qualitative research which focuses on the BBCT learning management of Early Childhood Islamic Education’ Material in BCC Ungaran Kindergarten.The subject of this research is the principal and teachers. The method of collecting data is observation, interview, and documentation. And data analysis technique used in this research is inductive analysis method.The results of this research show that BBCT learning management on Early Childhood Islamic Education’ Material in BCC Ungaran Kindergarten is good, because it based on the regulation from Permendiknas (Regulation from the Ministry of Education Affairs of Indonesia) No. 58 Year 2009 of standard contents and evaluation, include: planning, actuating, and learning evaluation. The supporting factors of the BCCT learning management are facilities, such as: buildings, classrooms, teachers’ rooms, giving reward for the best achievement teachers (the funding comes from the institution); BCCT training for one week in Istiqlal, Jakarta. Then, unsupporting factors of BCCT learning management are the limited media of learning and the number of teachers, so that the learning process is still not maximal. Supporting games are limited too, so students do not have options to play with.Keywords: BCCT Learning Management, Islamic education, early childhood education AbstrakPenelitian ditujukan untuk mengetahui manajemen pembelajaran BCCT (Beyond Center and Circle Time) materi Pendidikan Agama Islam pada anak usia dini di TK BCC (Bina Citra Cendekia) Ungaran serta mengetahui faktor pendukung dan penghambat manajemen pembelajaran BCCT materi Pendidikan Agama Islam pada anak usia dini di TK BCC Ungaran. Penelitian ini termasuk penelitian kualitatif yang fokus studinya pada manajemen pembelajaran BCCT materi Pendidikan Agama Islam pada anak usia dini di TK BCC Ungaran. Subyek penelitiannya adalah Kepala sekolah dan guru. Metode pengumpulan data adalah observasi, wawancara, dan dokumentasi. Dan teknik analisis datanya adalah teknik analisis induktif. Hasil temuan penelitiannya menunjukkan bahwa manajemen pembelajaran BCCT materi Pendidikan Agama Islam anak usia dini di Tk BCC Ungaran sudah baik karena sesuai dengan peraturan Permendiknas No. 58 Tahun 2009 tentang standar isi dan penilaian yang meliputi: perencanaan, pelaksanaan,  dan evaluasi pembelajaran. Faktor pendukung manajemen pembelajaran BCCT adalah sarana dan prasarana seperti: gedung, ruang kelas, ruang guru, jenis-jenis sentra serta pemberian reward bagi guru yang berprestasi dari lembaga yaitu pelatihan pembelajaran BCCT selama 1 minggu di Istiqlal Jakarta. Sedangkan faktor penghambat manajemen pembelajaran BCCT adalah jumlah guru dan media pembelajaran yang terbatas sehingga pembelajaran kurang maksimal, dan keterbatasan permainan pada setiap pijakan sehingga anak didik tidak banyak mempunyai pilihan dalam permainan yang dinginkan. Kata kunci: manajemen pembelajaran BCCT, pendidikan Islam, pendidikan anak usia dini